Pathogen Threat and In-group Cooperation - Imada, Hirotaka; Mifune, Nobuhiro (Frontiers in Psychology, 2021)
Disease-causing parasites and pathogens play a pivotal role in intergroup behavior. Previous studies have suggested that the selection pressure posed by pathogen threat has resulted in in-group assortative sociality, including xenophobia and in-group favoritism. While the current literature has collated numerous studies on the former, strikingly, there have not been much research on the relationship between pathogen threat and in-group cooperation. Drawing upon prior studies on the function of the behavioral immune system (BIS), we argued that the BIS may facilitate cooperation with in-group members as a reactive behavioral immune response to pathogen threat. More specifically, we held that individuals may utilize cooperative behavior to ensure that they can receive social support when they have contracted an infectious disease. We reviewed existing findings pertaining to the potential role of the BIS in in-group cooperation and discussed directions for future studies.